Black and Brown Education in America: Integration in Schools, Neighborhoods, and Communities - Hadi-Tabassum, Samina; Driver, Persis (Lexington Books, 2023)
Black and Brown Education in America: Integration in Schools, Neighborhoods, and Communities is a decade long ethnographic study of Maywood, Illinois, and the impact of its recent demographic shift from a historically Black middle-class suburb outside of Chicago with roots in the Black Panther Party to, now, a community with a growing Latinx population. It explores the intersection of race, culture, and language—and the ensuing Black-Brown identity politics—as well as the role of community organizations such as interracial faith-based churches and embattled school boards. Against a backdrop of racial tensions and heightened violence, the book also addresses transformative, liminal spaces where coalition building and collaboration bring the Black and Latinx communities together around common causes and unified goals.